PLAN ESTRATÉGICO DE MARKETING PARA LA EMPRESA DE LACTEOS “LACTOFINO” DE LA CIUDAD DE LOJA, PERIODO 2018 – 2021 - Maza Robles, Katty Amparito (2018)
This research has as main objective to elaborate a Strategic Marketing Plan for the company "LACTOFINO" of the city of Loja. For the preparation of the thesis work, a procedure was used to achieve the objectives; same as it is, of the deductive method to carry out the analysis of the PESTE factors and of the 5 forces of Michael Porter, in order to carry out the external and competitive analysis of the organization; in the internal diagnosis, an analysis was made of each of the marketing variables (product, price, place, promotion); For this analysis techniques were used, such as direct observation, the interview addressed to the owner manager and two types of surveys. Based on the results obtained, through the different analyzes carried out of the business environment of the company "Lactofino", the EFE matrix was elaborated, which provided a weighted value of 2.62 and the Competitive matrix with a value of 2.70, with these results appreciate that the company is competitively positioned and is taking advantage of opportunities to minimize the impact of threats. Then, through the internal diagnosis, the analysis of Marketing Mix of the company Lactofino was carried out, where the BCG matrix was used to carry out a study of the portfolio of products that it offers, where a growth of 43.62% was evidenced when performing the comparison of the income of 2016 and 2017. It was also noted that the Yogurt is the flagship product of the company under study, since it has a strong participation of 64.85% in sales of the company and a relative share in the market of 2.83%, being clear that this is the product that generates greater income to the organization. The strengths and weaknesses of the same were also determined, obtaining as a result the Matrix 5 EFI with a weighted value of 2.94, in which it was appreciated that "Lactofino" is at a stable level since there is a predominance of Strengths over Weaknesses, but it needs to improve and take advantage of its Strengths efficiently to overcome the weaknesses existing in it. In the discussion based on the internal and external analysis, the High Impact Matrix (SWOT) was built and the FO, DO, FA, DA combination was made, obtaining as a result the approach of 3 strategic objectives and the business philosophy proposal, followed by made the annual operative plan, where the proposed objectives were developed, which are; The first objective is the expansion of the marketing and distribution channel of the company, the second objective is to develop post-sale activities, the third objective is to develop a promotional plan with advertising actions; where in each objective the strategy, goals, tactics and times could be captured, which will allow carrying out the plan; In this way, the general budget for the implementation of the Strategic Marketing Plan was drawn up, which has a total cost of $ 5,057.70. Finally, the pertinent conclusions and recommendations of the investigation were made, which has been formulated attending the needs of the company "LACTOFINO", focused on allowing the use of resources to achieve the growth, development and positioning of the company in the market.